Legal Certainty in Resolving Medical Malpractice Issue in Indonesia: A Review of the 2023 Health Law - Purwanto, Agus; Yusdiansyah, Efik; Kurrohman, Taufik; Ginting, James Davidta (Sinergi International Journal of Law, 2026)
Medical malpractice disputes can occur in health services, treatments, actions, and care when patients feel disadvantaged or do not get the results they expected. It often arises when there are patients who are sick or unhealthy, then receive medical/medical actions that cause their illness to not heal or even become sicker or can also cause disability to the patient and even death or death. Medical malpractice disputes are disputes about bad practices, namely doing what should not be done or not doing what should be done. This incident often occurs in health services, both in hospitals, health centers, clinics, and even in independent practice places that end up in court. The purpose of the study is to understand and analyze the implementation of health law in Indonesia in resolving medical malpractice disputes with a legal certainty approach based on Law Number 17 of 2023 in conjunction with Government Regulation Number 20 of 2024, to understand, analyze, and seek proposals on what government policy should be in regulating the settlement of medical malpractice. The research method used is descriptive analysis with a normative legal approach through library and field research with data collection techniques through literature studies. Results of the study show that the policies contained in Law Number 17 Year 2023 still lack clarity because the law has yet to establish a precise and authoritative definition of medical malpractice which results in there being no legal certainty.